Greyhound [videorecording (DVD)] - Hanks, Tom; Hanks, Tom; Forester, C. S. (Cecil Scott), 1899-1966 (Columbia Pictures, 2020)
Based up on the novel "The Good Shepherd" by C.S. Forester. "Several months after the U.S. entry into World War II, an inexperienced U.S. Navy commander must lead an Allied convoy being stalked by a German submarine wolf pack. -- Container.